Echoes of Empire: Excavating the Colonial Roots of Britain’s “War on Gangs” - Nijjar, Jasbinder S. (Social justice, 2018)
The entanglement between notions of Blackness and gangs in Britain suggests that Black people exhibit some supposed compulsion for criminality collectively, as well as individually. This commentary critiques the criminalization of (young) Black individuals as gang members and the corresponding racialization of antigang policing and punishment measures through Britain’s history of colonial control and exploitation. I argue that the myth of collective Black criminality and the incorporation of clusters of Black individuals into an expanding prison labor market via joint enterprise relate to the criminalization and collective punishment of castes and tribes by the British colonial state in India. The resonance of Britain’s destructive past in present-day antigang initiatives makes it even more necessary to abolish gang databases, to question the validity of the idea of “the gang,” to review the convictions administered under joint enterprise, and to repeal the doctrine of common purpose itself.